2006
DOI: 10.1074/jbc.m600474200
|View full text |Cite
|
Sign up to set email alerts
|

Control of Template Positioning during de Novo Initiation of RNA Synthesis by the Bovine Viral Diarrhea Virus NS5B Polymerase

Abstract: The RNA-dependent RNA polymerase of the hepatitis C virus and thebovineviraldiarrheavirus(BVDV)isabletoinitiateRNAsynthesis de novo in the absence of a primer. Previous crystallographic data have pointed to the existence of a GTP-specific binding site (G-site) that is located in the vicinity of the active site of the BVDV enzyme. Here we have studied the functional role of the G-site and present evidence to show that specific GTP binding affects the positioning of the template during de novo initiation. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…that the initiation platform might be provided by this GTP rather than directly by the Pestivirus polymerase. This hypothesis has been confirmed to some extent by D'Abramo et al (44), who found that this GTP seemingly stabilizes the interaction between the 3Ј end of the template and the priming nucleotide. A similar phenomenon could also explain our observations with the HCV-NS5b S556K mutants.…”
Section: Discussionsupporting
confidence: 64%
“…that the initiation platform might be provided by this GTP rather than directly by the Pestivirus polymerase. This hypothesis has been confirmed to some extent by D'Abramo et al (44), who found that this GTP seemingly stabilizes the interaction between the 3Ј end of the template and the priming nucleotide. A similar phenomenon could also explain our observations with the HCV-NS5b S556K mutants.…”
Section: Discussionsupporting
confidence: 64%
“…It, furthermore, requires a "platform" to support the first nucleotide, which has to move out of the active center upon addition of the third base. This platform has not been clearly identified in the structure of the polymerase, but it might be provided by the C-terminal linker sequence (Harrus et al 2010) or by the beta flap in coordination with a GTP bound close to the active site, as suggested for pestiviruses (Lescar and Canard 2009;Choi et al 2004;D'Abramo et al 2006). Such a role of coordinating GTP in stabilizing the initiation complex might also explain the strong stimulating effect of high GTP concentration on de novo initiation of NS5B in vitro (Lohmann et al 1999b;Harrus et al 2010;Ranjith-Kumar et al 2003).…”
Section: Steps Of Rna Synthesismentioning
confidence: 99%
“…Polymerase activities of some viruses, such as Influenza virus, Bovine viral diarrhea virus, Hepatitis C virus and GB virus-B, are initiated by dinucleotides due to priming the transcription initiation [41], [53], [54], [55]. Additionally, the study using rotavirus open cores showed that GpG, which complements the sequences of the 3′ end of rotavirus G8 ‘plus’ strand RNA, forms initiation complexes with VP1 and template ssRNA to initiate ‘minus’ strand synthesis [32].…”
Section: Resultsmentioning
confidence: 99%